A comparison of finite element computations and an analytical approach for determining hull-induced underwater-radiated noise - Andresen-Paulsen, Gyde; von Bock und Polach, Rüdiger Ulrich Franz; Donderer, Matthias (American Society of Mechanical Engineers, 2022)
Underwater-radiated noise (URN) of shipping significantly affects marine wildlife and can be a substantial but unwanted signature. Structure- and air-borne noise induced by motions of the main engine lead to a vibrating ship hull that radiates underwater sound. However, until today it is not yet fully understood which structural parameters influence the hull-induced underwater noise radiation, and to what extent. Acoustic tests suffer from long lead times and require high effort, i.e., cost-intensive measuring systems and high personnel costs for setting up and conducting measurements, filtering out background noises, etc. Additionally, they are not well-suited for systematic studies, e.g., for varying geometry parameters. Numerical simulations can serve as a cost-efficient and versatile alternative but their validation is impeded by a lack of available and suitable experimental data. Here, a first step is presented towards validated numerical simulations for investigating the impact of each structural parameter as well as their coupling to URN. Finite element simulations are conducted comparing results with an analytical solution for underwater sound radiation of an infinite plate. The simulations show a good agreement with the analytical solution. Nonetheless, the degree of agreement between the two approaches depends significantly on the boundary conditions as well as on the setup of the numerical model. The analytical solution is valid for an infinite plate and an unconfined fluid domain, by setting boundary conditions in a numerical model these assumptions can be included. Based on the validated numerical model of an infinite plate, a bottom-up approach can be applied, for further investigations of various parameters of more complex structures regarding their influence on URN.